Cobalt Doped Titanium Dioxide Nanoparticles: Synthesis, Characterization and Electrocatalytic Study. Issue 6 (1st April 2014) - Bagheri, Samira; Chekin, Fereshteh; Hamid, Sharifah Bee Abd
Abstract In this work, green synthesis of cobalt doped titanium dioxide (Co‐TiO2) has been carried out in aqueous medium using gelatin. The Co‐TiO2 particles have been characterized using transmission electron microscopy (TEM), X‐ray diffraction (XRD), energy dispersive X‐ray (EDAX), FT‐IR spectroscopy and voltammetry techniques. XRD results show pure Co‐TiO2 and TiO2 powders with average crystallite size about 12 nm and 15 nm, respectively. Co loaded in TiO2 hasn't influence crystalline structure. Moreover, efficient Co‐TiO2‐based anode was fabricated by casting of the Co‐TiO2 solution on glassy carbon electrode (Co‐TiO2/GCE). The electrocatalysis of oxygen evolution reaction (OER) at Co‐TiO2/GCE has been examined using linear scanning voltammetry (LSV) in alkaline media. The OER is significantly enhanced at Co‐TiO2/GCE, as demonstrated by a negative shift in the LSV curve at the Co‐TiO2/GCE compared to that obtained at the unmodified one. The value of energy saving of oxygen gas at a current density of 5 mA cm−2 is 12.6 kW h kg−1. The low cost as well as the marked stability of the modified electrode make it promising candidate in industrial water electrolysis process.